(untitled) (Web of Teachers: Inderscience Research, 2026)
This study examines the influence of copper (Cu) and manganese (Mn) microelements supplied through the mineral complex Introvit WS on growth performance, hematological indices, and selected biochemical parameters of Karakul lambs. The experiment was conducted on 20 female Karakul lambs of the Jaydari type, divided into control and experimental groups. Lambs in the experimental group received Introvit WS at a dose of 10 g/L of drinking water for four consecutive days. Live body weight dynamics, morphological blood parameters, and serum biochemical indicators were analyzed on days 30, 60, and 90. The results demonstrated an increase in average live body weight by 100–200 g in the experimental group compared to the control. Erythrocyte count and hemoglobin concentration increased by 7–14%, while serum copper and manganese levels significantly increased, indicating improved mineral metabolism. The findings confirm that mineral supplementation with Cu and Mn positively affects the physiological status of Karakul lambs and contributes to improved adaptation and productivity.